Introduction to the Nervous System - Frank Reilly (Association of American Medical Colleges, 2011)
Abstract An interactive tutorial that serves as an introduction to the nervous system and the nomenclature used for classification was developed in Macromedia Flash and Viewpoint for distribution to first-year medical and dental students. The objective was to stimulate knowledge acquisition and retention by creating drill-and-practice exercises that focus on cranial and spinal nerve pathways including details about neurological deficits and tests of diagnostic and prognostic importance. Active learning was achieved by providing learners with opportunities for repetition and self-assessment through immediate feedback and quizzes. Content delivery consists of eleven objective-driven tutorial units with associated sound files, animated diagrams, labeled images, a glossary, e-flashcards, patient simulations for physical examination, nine patient-based case studies, and five Jeopardy-style games in the format of NBME subject examinations. The tutorial complements didactic and practical (dissection) activities of beginner health care professionals enrolled in human structure courses. It is best used in conjunction with lectures and labs reinforcing didactic and practical learning experiences. Convenient access also can be provided to learners reviewing for clinical certification and licensure examinations or to patients conferring with practitioners about their own neurological disorders. Since deployment of the courseware in 2001, significantly more students (8%; p < .05) scored correct answers on written block exam questions prepared by the same instructor-content expert. This study was a retrospective review of existing data that summarized the exam performance of 856 first-year medical students on 228 exam questions over a 9-year period. The experimental learner groups were exposed to didactic lectures, dissection labs, and both web-based lecture notes and interactive learning objects, while the control learner groups were restricted to didactic lectures and the dissection labs only. Student surveys using an instructional design questionnaire and a five-point Likert scale rated the virtual patient simulations the highest (p < .05) among the interactive resources provided for the preclinical human structure course.